Communication and Empathy Skills: Essential Requisites for Patient-Centered Radiology Care - Fatimah Abdulrahman Kariri,; Rawan Ghazi Alshaiban,; Ghaida Bakheet Hamdan Albalawi,; Taghreed Saeed Ali Alshahrani,; Ahmad Saeed Al-Qaflah,; Nadia Hassan Giman,; Khaled Mubarak Al Saad,; Ali Hasan yahya zalia,; Meznah Mohammed Alanazi,; Awatif Salem Alqahtani,; Nada Mohammed alkhunain, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Radiology, traditionally seen as a technical and behind-the-scenes specialty, is evolving towards a more patient-centered approach that emphasizes communication and empathy. This shift is driven by the growing recognition of the importance of patient satisfaction, trust, and involvement in healthcare decisions. Effective communication and empathy in radiology enhance patient understanding, reduce anxiety, improve diagnostic accuracy, and foster stronger relationships between patients, radiologists, and referring clinicians. However, implementing these principles presents challenges, including time constraints, high workloads, limited training, and cultural or institutional barriers. Strategies to overcome these obstacles include incorporating communication and empathy training into radiology curricula, leveraging technology such as telemedicine and patient-centered imaging reports, promoting institutional support for patient engagement, and fostering multidisciplinary collaboration. Case studies and evidence of success demonstrate the tangible benefits of these approaches, including increased patient satisfaction, improved outcomes, and reduced malpractice risks. Additionally, advancements in artificial intelligence (AI) and telehealth offer opportunities to streamline workflows, allowing radiologists to dedicate more time to patient-centered activities. Looking to the future, radiology will continue to evolve as a specialty where technical expertise is complemented by strong interpersonal skills, enabling radiologists to play a more visible role in patient care. By embracing this patient-centered vision, radiologists can enhance the overall healthcare experience, ensuring that patients feel valued, informed, and supported throughout their medical journey.